Epistemologi Kritis Konstruktif ke Arah Pembangunan Metodologi dan Metode: Constructive Critical Epistemology Towards the Development of Methodology and Methods - Sahadewa, Ngurah Weda; Wahyudi, Imam (Jurnal Filsafat Indonesia, 2024)
Constructive is a one of the key words in this research which is find of the precision meaning. The meaning of critical constructive can be developed by dimensions of epistemology and the dimensions of epistemology has an influence for the progress of the way of critical thinking. The constructive in the critical thought can be developed by self-critical constructive and critical constructive for the critical self-development. The method in philosophy can be developed by the method of every scientific at all. It means that first, the truth of knowledge based on reality. Second, the truth of reality not only about the fact but also about the construction. Third, epistemology that can be critical constructive if there is a correlation with the actuality or reality. The truth can be proved. If examined more deeply, there will be detailed errors regarding the actual ability of philosophy to understand the crucial relationship between reality and epistemologically constructed research activities. Therefore, the importance of this research is to produce basic provisions for the role of constructive critical epistemology to be developed as an important part of the development of methodology and methods, especially in the field of philosophical scientific studies. For this reason, basic methodological and methodical tools are needed based on constructive critical epistemology so that constructive critical epistemology obtains its implementation value in a constructive manner.